Does early surgery imply a critical risk for patients with Grade III acute cholecystitis?. Issue 1 (23rd March 2020) - Kohga, Atsushi; Okumura, Takuya; Yamashita, Kimihiro; Isogaki, Jun; Kawabe, Akihiro; Kimura, Taizo
Abstract: Background: For patients with Grade III acute cholecystitis (AC), several factors have been proposed in the 2018 Tokyo guidelines as caution signs in performing early surgery. However, these factors have not been externally validated in detail. Methods: This retrospective study examined 35 patients who had been diagnosed with Grade III AC and treated with laparoscopic cholecystectomy between January 2008 and July 2019. The patients were allocated into an early group (patients who underwent surgery within 7 days of admission, n = 28) and a delayed group (patients who underwent surgery at least 8 days after admission, n = 7). Comparisons were made between these groups. Results: No patients died. Significantly more patients required a conversion to open surgery (0% vs 28.5%, P = .003) or conversion to subtotal cholecystectomy (25.0% vs 71.4%, P = .020) in the delayed group than in the early group, and the total length of postoperative stay was significantly longer in the delayed group (11.4 vs 27.2 days, P = .001). The presence of negative predictive factors or risk factors listed in the 2018 Tokyo guidelines was not associated with death or postoperative complications. Conclusions: Early surgery was considered appropriate and feasible for select patients who had Grade III AC and preoperative risk factors.